From Palace Lady to Tara: Exploring the Transformation of the Female Role in Buddhist Belief through the Sinicization of Buddhism - Yun Wang; Shaojiao Zhang (Religions, 2024)
This paper argues that the historical process of the Sinicization of Buddhism and the evolution of the value of female roles in Buddhist beliefs have advanced hand in hand; the more Buddhism becomes Sinicized, the higher the status of women in Buddhist beliefs becomes. To some extent, the Sinicization of Buddhism can be considered a feminization process. Female roles in Buddhist beliefs are often passive objects and marginal positions that are uncertain and continuously presupposed by others. This article starts from a cultural, philosophical perspective, aiming to examine the internal logic of the evolution of female roles in Buddhist beliefs. In terms of individual experience, the highlighting of the identity as a “subject” of sexual desire makes women a necessary but insufficient prerequisite “option” for guiding male sexual desire—in Indian Buddhist beliefs, women’s enlightenment involves both reflecting on sexual desire itself and negating their own gender disadvantage. As Buddhism spread worldwide, Western Buddhist traditions laid the foundation of Buddhist belief on “sacred images”, while various local cultural genes infiltrated the imagination of “Western Buddhist nations”. The Buddha’s gender orientation achieved a transcendence of both male and female or a bilateral blend, leaning more towards female. Ultimately, from the perspective of family identity, in a Chinese Buddhist belief world organized by the patriarchal system, the unique role of women in the family—“mother”—pushes Buddhist belief back to the scene of the emotional world.